A guidance framework to aid in the selection of nursing and midwifery care process metrics and indicators - Brenner, Maria (My University, 2019)
Aim: To describe the development of a guidance framework to assist nurses and midwives in selecting nursing and midwifery care process metrics and indicators for use in practice. Background: Process metrics are measures of care provision activities by nurses and midwives. Methods: Phase 1 was a rapid review assessment of the literature conducted to identify an initial framework. Six electronic databases were searched with Google Scholar and reference tracking performed. Phase 2 was expert review of the developing framework by nursing and midwifery experts in practice, academia and an international expert in quality care metrics. Results: The literature assessment yielded 28 papers with 59 metric attributes identified. From this, a six-domain framework was developed. Following expert review, the framework was reduced to four domains: “Process Focused,” “Important,” “Operational” and “Feasible.”. Conclusions: This is the first framework specifically to guide nurses and midwives in selecting nursing and midwifery process metrics and indicators
Keywords: guidance framework; nurses and midwives; care process metrics and indicators; Nursing midwifery care process indicators; Nursing midwifery care process metrics; Quality indicators; Selection framework